The colonial legacy of education: Evidence from of Tunisia - Mhamed Ben Salah; Cédric Chambru; Maleke Fourati (University of Zurich, Department of Economics, 2024)
This paper uses spatial variations in the enrolment rate of Tunisian pupils in 1931 to estimate the weight of colonial history on medium- and long-run educational attainment. We assemble a new dataset on the location of public primary schools and the number of pupils and teachers, together with population data for 1931. We match these data with information on education at the district level, derived from two population censuses conducted in 1984 and 2014. We find that a one per cent increase in the enrolment rate in 1931 is associated with a 2.37 percentage points increase in the literacy rate in 1984, and a 1.89 percentage points increase in 2014. We further investigate the exposure to colonial public primary education across different age cohorts. We find that our results are mainly driven by older generations, and tend to fade for younger cohorts. While we provide qualitative evidence that a cultural transmission of education may have contributed to this persistence, we also argue that the continuous effort and investment made by Tunisian governments to achieve universal primary enrolment best explain the decline in spatial disparities in educational attainment.
Keywords: D10; H52; I25; I28; N37; N47; Z10; 330; Colonial investment; Colonial settlers; Primary education; Literacy; Tunisia